KAJIAN SOSIOLINGUISTIK TERHADAP UJARAN BAHASA MAHASISWA - Siti Restu Nur Fadlillah Haq; Rochmat Sudrajat; Dida Firmansyah (IKIP Siliwangi, 2020)
The use of language in life greatly affects the articulation of communication and interactions between humans. This interaction provides a unity to connect a difference. Therefore, diversity in language is unique in the field of communication. The important role of communication tools helps the articulation of social life. The use of language in educational institutions is very vulnerable to being influenced by the environment. This causes the mixed dialect used by Indonesian students to be very unique and diverse. In general, this study aims to determine the diversity of languages used by various students in educational institutions and their environment, especially Indonesian students. Specifically, the purpose of this article is to (1) describe the dialect of Indonesian students 'speech, and (2) to describe the use of code mixing for Indonesian students' speech. Researchers used descriptive qualitative methods as a research method and sociolinguistic approach. The research was conducted in order to solve problems faced in the field by using several stages of data collection (1) taking samples of the spoken language used by Indonesian students, (2) analyzing the use of dialects and code mixing on the spoken language of Indonesian students. Thus, the results of the study show that the use of dialects and mixed codes in communication that are often used by Indonesian students is evident. This study also describes the linguistic behavior carried out by Indonesian students directly through oral.